Ideologia e direito : a influência neoconservadora na produção normativa sobre direitos sexuais e reprodutivos entre os anos de 2019 e 2022 no Brasil - Pereira, Hellen Alessandra Dantas (2024)
The present study addresses the advances of the neoconservative movement in the legal-normative scope, emphasizing its ideological influence. Amid a context marked by political polarization and expansion of agendas contrary to human rights in Brazil, several norms were produced or changed between 2019 and 2022. The following problem arises: in what form was the neoconservative ideology incorporated by the Bolsonaro government, and has it impacted the normative discourse on sexual and reproductive rights? To answer this question, we start with the hypothesis that this ideology negatively influenced the implementation of these rights, although the basis used for its change was political neutrality. Therefore, this research aims to analyze the neoconservative expansion in the field of Law, considering the ideological functioning present in the normative discourse as a general objective of analyzing. To assist in this search, the following specific objectives were selected: a) understand neoconservative movements and their agendas; b) verify the ideological influence on the subjects; c) demonstrate the relationship between neoconservative ideology and the Law; d) verify the regulatory changes on sexual diversity and reproduction made during the Bolsonaro Government; e) describe the normative texts, their objectives and provisions; f) analyze the meaning relationships extracted from the standards in question, in order to verify the compliance of their provisions with the protection of sexual and reproductive rights in Brazil. To make this investigation possible, we use the methodology of French Discourse Analysis, according to legal semiotics, in its pragmatic dimension, with the help of the scientific-systemic semiotic method. Therefore, this exploratory, descriptive study with a qualitative approach developed from examining three categories: multitextuality, coherence, and normative silence. Finally, it is concluded that neoconservative ideology negatively influenced the normative texts examined in order to deprive rights.